Financial Performance Factors of MSMEs: An Analysis of the Mediating Effects of Government Support - Adillah, Egga (International Economic Conference of Business and Accounting, 2024)
MSMEs are the cornerstone of the national economy, playing a vital role in driving economic growth. This study provides an in-depth analysis of how financial digitalization, Financial Inclusion, and access to Capital enhance the financial performance of MSMEs, focusing on the strategic role of government support as a mediating variable that strengthens these relationships. The type of research used in this research is quantitative, and the subject of this research is MSMEs in Pontianak City. The data analysis technique used is the Structural Equation Model (SEM) with the Smart PLS statistical test tool. The results of this study show that Financial digitalization and access to Capital positively impact MSME performance through government support as a mediator. However, government support cannot mediate the effect between financial Inclusion and MSME performance.